Structural analysis of CdO thin films prepared by PCI method with varied concentrations of solution - Ida Usman; Waode Sukmawati Arsyad; La Ode Kadidae (Pascasarjana Universitas Sulawesi Tenggara, 2023)
Research about CdO thin film deposition has been conducted using the chemical immersion technique. The deposition process was conducted by immersing the glass substrate into the solution couple of cadmium acetate dehydrate (Cd(CH3COO)2.2H2O) by flitting with sodium hydroxide (NaOH). The solutions' concentrations were varied to investigate the influence of the concentration ratio of both solutions on the characteristic of resulted in CdO film. To strengthen the atomic bonding and discharge the rest of the water content, the resulting films were then heated in the furnace at 225 oC. Based on the measurement result of SEM-EDX, the Cd mass percentage in CdO thin films is quantitatively dependent on the concentration of cadmium acetate dehydrate solution. Also, the results of optical band gap determinations show that the increasing ratio of Cd to O content was a tendency in linear relation with the stricture of its optical band gap.